Partners Experience Consequences, Too: A Comparison of the Sexual, Relational, and Psychological Adjustment of Women with Sexual Interest/Arousal Disorder and Their Partners to Control Couples. Issue 1 (30th November 2018) - Rosen, N. O.; Dubé, J. P.; Corsini-Munt, S.; Muise, A.
Abstract: Introduction: Women diagnosed with female sexual interest/arousal disorder (FSIAD) report lower health-related quality of life, more depressive symptoms, and lower sexual and relationship satisfaction compared with healthy control subjects. Despite the impact of FSIAD on women's sexuality and the inherently interpersonal nature of the sexual problem, it remains unclear whether the partners of women with FSIAD also face negative consequences, as seen in other sexual dysfunctions. Aim: The aim of this study was to compare the sexual, relational, and psychological functioning of partners of women with FSIAD (as well as the women themselves) to their control counterparts. We also compared women with their partners within the FSIAD and control groups. Methods: Woman diagnosed with FSIAD and their partners (n = 97) and control couples (n = 108) independently completed measures of sexual desire, sexual distress, sexual function, sexual satisfaction, sexual communication, relationship satisfaction, depression, and anxiety. Main Outcome Measure: Main outcomes included: Sexual Desire Inventory-2; Female Sexual Distress Scale; Female Sexual Functioning Index; International Index of Erectile Functioning (IIEF), Global Measure of Sexual Satisfaction; Dyadic Sexual Communication Scale; Couple Satisfaction Index; Beck Depression Inventory-II; State-Trait Anxiety Inventory-Short Form. Results: Partners of women with FSIAD reported lower sexual satisfaction, poorer sexual communication, and higher sexual distress compared with control partners. Male partners of women with FSIAD reported more difficulties with orgasmic and erectile functioning and lower overall satisfaction and intercourse satisfaction on the IIEF compared with control partners. Women with FSIAD reported lower sexual desire and satisfaction, and higher sexual distress and depressive and anxiety symptoms, in comparison to both control women and their own partners, and they reported poorer sexual communication compared with control women. Women with FSIAD also reported lower sexual desire, arousal, lubrication, and satisfaction, and greater pain during intercourse on the Female Sexual Function Index compared with control women. Clinical Implications: The partners of women with FSIAD also experience negative consequences—primarily in the domain of sexuality. Partners should be included in treatment and future research. Strength & Limitations: This is the first study, to our knowledge, to document consequences for partners of women with FSIAD in comparison to control subjects. This study is cross-sectional, and causation cannot be inferred. Most couples were in mixed-sex relationships and identified as straight and cis-gendered; results may not generalize. Conclusion: Findings suggest that partners of women with FSIAD experience disruptions to many aspects of their sexual functioning, as well as lower overall sexual satisfaction and heightened sexual distress.